Bacterial Lipopolysaccharides Structure, Chemical Synthesis, Biogenesis and Interaction with Host Cells - Knirel, Yuriy A.; Valvano, Miguel A. (Springer Vienna : Imprint: Springer, 2011)
The bacterial lipopolysaccharide also known as endotoxin is exhaustively covered in the present work. Central emphasis is placed upon the fine chemical structure of the lipopolysaccharide and its significance for understanding their activity and function. In particular, the role it plays in the interaction of bacteria with other biological systems is examined. New aspects of their physicochemical biology are introduced and updates to the current knowledge concerning the lipopolysaccharide are provided. This important class of biomolecules has recently attracted the attention of many investigators, in particular for understanding its involvement in innate immunity, toll-like receptor recognition and intracellular signaling.